2018
DOI: 10.1101/284000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Switch-like activation of Bruton’s tyrosine kinase by membrane-mediated dimerization

Abstract: The transformation of molecular binding events into cellular decisions is the basis of most biological signal transduction. A fundamental challenge faced by these systems is that protein-ligand chemical affinities alone generally result in poor sensitivity to ligand concentration, endangering the system to error. Here, we examine the lipid-binding pleckstrin homology and Tec homology (PH-TH) module of Bruton's tyrosine kinase (Btk) Using fluorescence correlation spectroscopy (FCS) and membrane-binding kinetic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…Interaction with Nef may relieve this negative regulatory influence by displacing the PH domain, in a manner analogous to regulatory SH3 domain displacement associated with Nef-dependent activation of the Src-family kinase, Hck (16,40). Furthermore, membrane PIP3 may also drive Btk dimer formation as part of a unique activation mechanism not shared by Itk (41). In this case, Nef may exploit and enhance this natural mechanism of Btk activation by stabilizing preformed dimers at the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction with Nef may relieve this negative regulatory influence by displacing the PH domain, in a manner analogous to regulatory SH3 domain displacement associated with Nef-dependent activation of the Src-family kinase, Hck (16,40). Furthermore, membrane PIP3 may also drive Btk dimer formation as part of a unique activation mechanism not shared by Itk (41). In this case, Nef may exploit and enhance this natural mechanism of Btk activation by stabilizing preformed dimers at the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The physical differences between events that increase proximity of MST1/2 kinase domains will affect both the level and lifetime of autophosphorylated MST1/2 and, thus, modulate the downstream response. Trans-autophosphorylation reactions inherently represent a positive feedback switch with the rate of activation dependent on the magnitude of the change in effective concentration (78)(79)(80)(81). Not all activating events will result in the same change in effective concentration; for example, based on linker lengths, homodimerization of MST1/2 will raise effective concentration of MST1/2 higher than complex formation with SAV1 (82).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the structural analysis of InsP 6 /PH domain complex showed that the PH domain of Btk has two InsP 6 binding sites (21). The occupation of both sites in PH domain is important for the activation of Btk by dimerization (21,53). One of them is a canonical binding site that is essential for binding to PtdIP 3 in the membrane.…”
Section: Discussionmentioning
confidence: 99%